Interstitial nephritis in avian pathology. - Nóbrega, C. (2013)
Introduction Interstitial nephritis often occurs in birds, associated with diverse aetiologies, including infectious and non-infectious ones. In the nephritis of infectious origin, we can highlight the viral origin, mainly avian nephritis virus (AVN), but also Newcastle disease, infectious bronchitis and Marek's disease and also nephritis of bacterial and parasitic origin. As non-infectious causes, we can point to the deposition of inflammatory proteins in the glomerular space that leads to glomerulonephritis. Moreover, pigeon are a growing specie in urban areas and their proximity with other birds, including poultry, favours propagation of diseases, however available studies on its health status and its possible interaction with other domestic specie are scarce, justifying increasingly deepening of cases in this species. Aim This work intends to make an update theme, using as examples two cases of interstitial nephritis in poultry, concomitantly with other common diseases. Material and methods Two birds with unspecific signs of lethargy and death occurring few hours later, were sent to the Laboratory of Pathology, Agrarian School of Viseu, to determine the cause of death. A detailed post-mortem examination was carried out, samples were taken and processed following the routine histopathological technique. Results No remarkable gross lesions were observed unless a slight congestion in one kidney. Microscopic examination revealed the presence of mononuclear cell infiltration in renal interstitium in one case and mixed inflammatory infiltrate in the other. Concomitantly, the birds had other common diseases, different in each case, discussing the significance of the presence of interstitial nephritis in birds as nonspecific secondary injury associated with other pathologies or specific and primary. Conclusion The presence of interstitial nephritis in a variety of avian diseases raises some questions, including why the kidney is so consistently affected. In mammals, there are several urinary pathologies that affect only the urinary system, but in birds, although this situation also exists, most urinary disorders are part of multi-systemic conditions. On the other hand, cases of pigeons with multisystem conditions, and given their role as transmitters of disease to other birds, represent an element of value to study nowadays.